Pacific families navigating responsiveness and children's sleep in Aotearoa New Zealand - Molly George (Elsevier, 2021)
The stakes for understanding sleep practices are rising as health inequalities related to sleep become more apparent. Pacific peoples in Aotearoa New Zealand face disproportionate challenges around poverty and health and sleep is one growing area of importance in addressing health inequalities. Through a qualitative study of 17 Pacific families in Aotearoa New Zealand, we provide a rare and valuable glimpse into the familial, cultural, social and economic context of sleep for Pacific families and children in New Zealand. These Pacific families uphold a core value of responsiveness to family, community, culture and faith. These values feed wellbeing in a variety of ways, especially when health is considered through Pacific, holistic frameworks. These families apply the same responsiveness to economic pressures, often taking on shiftwork. We show how responsiveness to family and culture, as well as limited economic means, permeates sleep practices within these Pacific households. These broader shaping factors must be acknowledged, considered, respected and integrated into any healthy sleep initiatives and interventions, in order to ensure benefit - and not harm - is achieved.